2017
DOI: 10.1007/s10853-017-1435-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the elongation, yield strength and magnetic properties of intermetallic FeCo alloy using spark plasma sintering

Abstract: Equiatomic FeCo alloys were densified using spark plasma sintering (SPS). Using a constant 50 MPa pressure, the sintering temperature and dwell times for the SPS process were optimised for different heating rates (50, 100, 300 ºC.min-1). All samples used in this optimisation process were analysed in terms of their mechanical and magnetic properties. Interestingly, for all heating rates, FeCo samples sintered at the highest temperatures (1100 ºC) without dwelling exhibited an increased tensile yield strength co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The importance of intermetallic compounds (IMCs) has been long recognized for their use in magnetic materials, [1][2][3] superconducting materials, [4][5][6] hydrogen storage, 7,8 shape-memory materials, 9 and heterogeneous catalysis. [10][11][12][13] IMCs have been reported to show improved selectivity to hydrogenation, 14,15 oxidation, 12,13 steam reforming, 16,17 and hydroformylation 18 compared to their monometallic counterparts, providing an effective alternative to the noble metal catalysts used in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of intermetallic compounds (IMCs) has been long recognized for their use in magnetic materials, [1][2][3] superconducting materials, [4][5][6] hydrogen storage, 7,8 shape-memory materials, 9 and heterogeneous catalysis. [10][11][12][13] IMCs have been reported to show improved selectivity to hydrogenation, 14,15 oxidation, 12,13 steam reforming, 16,17 and hydroformylation 18 compared to their monometallic counterparts, providing an effective alternative to the noble metal catalysts used in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we would like to discuss the magnetostriction and UTS of annealed Fe 29 Co 71 wire compared with the other magnetostrictive materials based on the earlier results. Figure 10 shows these characteristics with common Fe-based magnetostrictive materials such as Fe-Co system, Fe-Ga system, Fe-Al, and Tb-Dy-Fe alloys [8][9][10][11][12][13][15][16][17][18] reported so far. In general, there is a trade-off relationship between the amount of magnetostriction and the strength of Fe-based magnetostrictive alloys.…”
Section: Out = V W Output By Cyclic Compression Testmentioning
confidence: 99%
“…However, the fast heating rate of 300 • C.min -1 was effective in reducing grain size, therefore an increase in coercivity value was observed. Conflicting behaviour is observed when the sintering temperature is increased to 1100 • C, due to the reduction in volume fraction of the ordered state at faster heating rates, 6 and increase the grain size. Moreover, sintering at high temperature helps in releasing the coercivity dependent on residual stresses in the material which are introduced during mechanical pressing and causes more purification for structure.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…The detailed of microstructure study of FeCo alloy sintered following the above-mentioned sintering conditions are reported in our previous study on mechanical properties in Ref. 6.…”
Section: A Relative Density and Grain Sizementioning
confidence: 99%
See 1 more Smart Citation